Kesesuaian Ruang Terbuka Publik Sebagai Ruang Bermain Ramah Anak Berdasarkan Persepsi Masyarakat (Studi Kasus: Kecamatan Balikpapan Selatan) - Araminta, Bintang Atha; Astha, Dwinsani Pratiwi; Tufail, Dwiana Novianti; Jordan, Nadia Almira (COMPACT: Spatial Development Journal, 2023)
The Department of Population, Women Empowerment, and Child Protection of Balikpapan City found a lack of safe and comfortable play areas. However, in accordance with the Convention on the Rights of the Child that supports the status of Child-Friendly City, the right to play includes having green open spaces and playgrounds for children, including those with disabilities. Balikpapan City has several active green open spaces, such as the Three Generations Park, Traffic Park, and Smart Park, which provide public facilities for interactive activities, learning, and playing for children. This research aims to formulate guidelines for developing supportive elements of child-friendly play spaces in the public green open spaces of South Balikpapan District. This is done with specific standards to support the achievement of Child-Friendly City, particularly through the development of Child-Friendly Play Spaces (CFPS) as an important sub-indicator in achieving this status. The research uses a mean score method by distributing questionnaires to the community. The findings revealed that in these three parks, 8 variables were found to have poor conditions.